Medium dependent optical response in ultra-fine plasmonic nanoparticles. Issue 39 (28th September 2022) - Sørensen, Lasse K.; Khrennikov, Daniil E.; Gerasimov, Valeriy S.; Ershov, Alexander E.; Polyutov, Sergey P.; Karpov, Sergey V.; Ågren, Hans
Abstract : From an atomistic representation of the nanoparticle material we show the importance of surface layer influence and media on the interaction of ultra-fine plasmonic nanoparticles (≤ 8 nm) with radiation. Abstract : We study the influence of media on the interaction of ultra-fine plasmonic nanoparticles (≤ 8 nm) with radiation. The important role of the surface layer of the nanoparticles, with properties that differ from the ones in the inner part, is established. Using an atomistic representation of the nanoparticle material and its interaction with light, we find a highly inhomogeneous distribution of the electric field inside and around the particles. It is predicted that with an increase in the refractive index of the ambient medium, the extension of the surface layer of atoms increases, something that also is accompanied by an enhanced red shift of the plasmon resonance band compared to large particles in which the influence of this layer and its relative volume is reduced. It is shown that the physical origin for the formation of a surface layer of atoms near the nanoparticle boundary is related to the anisotropy of the local environment of atoms in this layer which changes the conditions for the interaction of neighboring atoms with each other and with the incident radiation. It is shown that a growth of the refractive index of the ambient medium results in an increase in the local field in the dielectric cavity in which a plasmonic nanoparticle is embedded and which is accompanied by a growth of the amplitude of the plasmon resonance. We predict that in the ultra-fine regime the refractive index sensitivity shows a decreasing trend with respect to size which is opposite to that for larger particles. With the applied atomistic model this work demonstrates close relations between field distributions and properties of ultra-fine nanoparticles.